Forum Ilmu Sosial Faculty of social science, universitas Negeri Semarang (2011)
Forum Ilmu Sosial is a journal that publishes scientific papers on the results of social science research covering the fields of sociology, anthropology, geography, history and education kewarganergaraan.?Forum Ilmu Sosial?has published continuously s
ince 2008 with registered number?ISSN 1412-971X?(print),?ISSN 2549-0745?(online).?The article contains writings lifted from the results of research and conceptual, both theoretical and applied social science.?Forum Ilmu Sosial is an open access journa
l and also available in print.